Effect of Crude Extracts from Ya Faek Lum (Vetiveria zizanioides (L.) Nash)Leaves on Growth of Curvularia lunata (Wakker) Boedijn - ศรประเสริฐ รัฐพล (KKU Science Journal, 2013)
Extraction of Ya Faek Lum (Vetiveria zizanioides (L.) Nash) leaves, Suratthani strain with ethanol 95% solvent yielded a crude extracts which was characterized by a concentrated-sticky, dark green color and pleasant aroma with 1.47% yield. This research studied the effect of crude extracts against Curvularia lunata (Wakker) Boedijn. The crude extract at 20,000 ppm showed the best inhibiting effect against C. lunata (Wakker) Boedijn, following by 15000, 10000, 5000 and 0 ppm respectively which had inhibited percentile 34.02, 24.63, 22.43, 9.14 and 0.00 respectively. The minimum inhibitory concentration of crude extracts against of C. lunata (Wakker) Boedijngrowth was equivalent to 0.125 mg/ml.